2014
DOI: 10.1038/ncomms4876
|View full text |Cite
|
Sign up to set email alerts
|

Dirac cones and Dirac saddle points of bright excitons in monolayer transition metal dichalcogenides

Abstract: In monolayer transition metal dichalcogenides, tightly bound excitons have been discovered with a valley pseudospin optically addressable through polarization selection rules. Here, we show that this valley pseudospin is strongly coupled to the exciton centre-of-mass motion through electron-hole exchange. This coupling realizes a massless Dirac cone with chirality index I ¼ 2 for excitons inside the light cone, that is, bright excitons. Under moderate strain, the I ¼ 2 Dirac cone splits into two degenerate I ¼… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

30
392
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 338 publications
(423 citation statements)
references
References 42 publications
30
392
1
Order By: Relevance
“…We observe that, as we increase transmission NA from 0.1 to 0.55, the extinction drops from 0.9 down to 0.6, while the exciton linewidth increases from 3 to 6 meV. We tentatively attribute this strong NA dependence to electron-hole exchange interaction induced modification of the exciton spectrum: it has been theoretically predicted that, due to this interaction, the p-polarized excitons would have a Dirac-conelike dispersion, leading to an energy splitting of s-and p-polarized excitons of order 3 meV for k ∼ ω exc =c [26,27]. To the best of our knowledge, the NA-dependent increase in linewidth that we report here provides the first evidence for this striking theoretical prediction.…”
Section: (C)mentioning
confidence: 88%
“…We observe that, as we increase transmission NA from 0.1 to 0.55, the extinction drops from 0.9 down to 0.6, while the exciton linewidth increases from 3 to 6 meV. We tentatively attribute this strong NA dependence to electron-hole exchange interaction induced modification of the exciton spectrum: it has been theoretically predicted that, due to this interaction, the p-polarized excitons would have a Dirac-conelike dispersion, leading to an energy splitting of s-and p-polarized excitons of order 3 meV for k ∼ ω exc =c [26,27]. To the best of our knowledge, the NA-dependent increase in linewidth that we report here provides the first evidence for this striking theoretical prediction.…”
Section: (C)mentioning
confidence: 88%
“…Polarization-resolved PL measurements yielded a valley-contrasting circular dichroism of less than 20% for both X 0 and X − resonances in all the flakes that were measured. As we argue below, the electron-hole exchange-induced mixing of the two valleys is possibly responsible for reducing the degree of circular dichroism 21,23 . Figure 2a shows the behaviour of X 0 at various B up to 8.4 T in the Faraday geometry (B z).…”
mentioning
confidence: 99%
“…The absence of valley coherence of the X − peak in monolayer WSe 2 has been attributed to the fast phase-rotation associated with this energy splitting 22 . Recently, it was theoretically shown that the corresponding exchange-induced modification of the trion dispersion ensures that the trion states with centre-ofmass momentum ∼ ±K carry a large Berry curvature 21 . If the trion can be considered as a strongly bound, charged quasi-particle, the exchange-induced Berry curvature (k) will be accompanied by a contribution to the orbital magnetic moment that is given by µ(k) = (e/2h) (k)δ ex for k ±K; here δ ex is the exchangeinduced splitting of the trion resonances.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This information allows us to estimate the ratio between T 1 and T 2 , leaving only two independent parameters in the model (Supplementary Section I). (We note that the partial degree of linear polarization has several possible origins, including intervalley scattering induced by defects/impurities, intravalley scattering, and the exchange interaction between excitons [23][24][25] . Within our model, we neglect possible initial depolarization effects in creating the valley excitation, in accord with the near-resonant character of our optical excitation.)…”
mentioning
confidence: 99%